2016
DOI: 10.1177/0886260516658757
|View full text |Cite
|
Sign up to set email alerts
|

An Updated Review of Institutions of Higher Education’s Responses to Sexual Assault: Results From a Nationally Representative Sample

Abstract: It has been more than a decade since Karjane, Fisher, and Cullen reviewed a nationally representative sample of Institutions of Higher Education (IHEs) and documented "sexual assault on college campuses" and "what colleges are doing about it." The current research aimed to examine the current state of IHE's response to campus sexual assault as well as any changes in IHE's response over the previous decade. To this end, the present study provides a comparison of data reported in Karjane et al. and 2015 data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(108 citation statements)
references
References 32 publications
3
100
0
Order By: Relevance
“…Campus victim advocates work for such centers and do work similar to rape crisis advocates in the community; they can provide therapy services and attend all steps of the formal reporting pathway. As of 2015, research found that 55 percent of a nationally representative sample of colleges employed on‐campus victim advocates (Richards, ). The same study found that 2‐year colleges were less likely to report having victim advocates and counseling services than were 4‐year institutions (Richards, ).…”
Section: Campus Policiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Campus victim advocates work for such centers and do work similar to rape crisis advocates in the community; they can provide therapy services and attend all steps of the formal reporting pathway. As of 2015, research found that 55 percent of a nationally representative sample of colleges employed on‐campus victim advocates (Richards, ). The same study found that 2‐year colleges were less likely to report having victim advocates and counseling services than were 4‐year institutions (Richards, ).…”
Section: Campus Policiesmentioning
confidence: 99%
“…As of 2015, research found that 55 percent of a nationally representative sample of colleges employed on‐campus victim advocates (Richards, ). The same study found that 2‐year colleges were less likely to report having victim advocates and counseling services than were 4‐year institutions (Richards, ).…”
Section: Campus Policiesmentioning
confidence: 99%
“…We invited Title IX officers from IHEs to participate in this study, because they have a specific federally mandated role on college campuses in relation to addressing CSAs, and they are typically one formal reporting mechanism for incidents of CSA (Richards, 2016). There was no contact page that listed all of the current Title IX officers in the U.S. from which we could generate our sample population; therefore, we manually constructed an e-mail list of IHE Title IX officers using the U.S. Department of Education's Campus Safety and Security website (U.S. Department of Education, n.d.).…”
Section: Samplementioning
confidence: 99%
“…Given that IHE response to CSAs is multifaceted and involves various stakeholders on and off campus (Karjane et al, 2005;Richards, 2016; Center for Research on Violence against Women [CRVAW], 2014), it is pertinent to know who was involved in planning the sexual assault CCSs. Of the Title IX officers whose institutions launched a survey in the 2014/2015 year, approximately 51.2% of the respondents reported that they, as the Title IX officer, were primarily responsible for planning the survey.…”
Section: Questionnaire Development Who Was Involved?mentioning
confidence: 99%
“…First, this study focused specifically on IHEs that offer at least a 4‐year degree. Richards () and Karjane et al () found that 4‐year institutions are generally most likely to comply with federal legislation regarding peer sexual violence among college students and thus are a reasonable place to begin this research. We stress the importance of continued research focused on identifying adopted mandates and best practices concerning sexual assault victimization and their alignment with feminist, victim‐centric organizational models at other IHE types including 2‐year institutions and those less than 2 years.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%